Tindak Tutur Imperatif dalam Percakapan Nonformal Mahasiswa FKIP Universitas Al-Khairat Palu - Syamsuddin, Syamsuddin; Efendi, Efendi; Syam, Akhmad (Jurnal Kreatif Online, 2020)
The purpose of this study was to describe the forms and strategies of imperative speech acts in non-formal conversations by FKIP students at Al-Khairat University, Palu. Subjects and data sources in this study were words (conversations) and actions carried out by FKIP students at Al-Khairat University Palu in informal conversations, and written sources in the form of scientific books/ magazines. This research used observation type data collection with the free competent involvement technique (SBLC) and note-taking technique. The data analysis used was the interactive model data analysis technique. The interactive model data analysis was carried out through 3 stages: data reduction, data presentation and drawing conclusions. The findings in this study have been sorted in terms of form and strategy. Speech forms consist of: 1) Imperative request speech, 2) Command imperative speech. 3) Imperative speech. 4) Imperative suggestion speech and 5) Imperative invitation speech. Meanwhile, the strategies used by FKIP students at Al-Khairat University Palu were 1) direct strategy and 2) indirect strategy.Â